9. (2x+3)(4x+5)

Use FOIL (first, outside, inside, last)

2x * 4x = 8x^2

2x * 5 = 10x

3 * 4x = 12x

3 * 5 = 15

8x^2 + 10x + 12x + 15

Now combine middle terms

8x^2 + 22x + 15

10. (4x-5)(3x-2)

4x * 3x = 12x^2

-2 * 4x = -8x

-5 * 3x = -15x

-5 * -2 = +10

12x^2 - 8x - 15x + 10

Now combine middle like terms

12x^2 - 23x + 10

Best my answer if you think I explained it better and went through all of the steps.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up